Coat protein is responsible for tomato leaf curl New Delhi virus pathogenicity in tomato - Vo, Thuy T. B.; Lal, Aamir; Nattanong, Bupi; Tabassum, Marjia; Qureshi, Muhammad Amir; Troiano, Elisa; Parrella, Giuseppe; Kil, Eui-Joon; Lee, Sukchan (Frontiers in Plant Science, 2023)
Tomato leaf curl New Delhi virus (ToLCNDV), a bipartite begomovirus belonging to the family Geminiviridae, causes severe damage to many economically important crops worldwide. In the present study, pathogenicity of Asian (ToLCNDV-In fromPakistan) and Mediterranean isolates (ToLCNDV-ES from Italy) were examined using infectious clones in tomato plants. Only ToLCNDV-In could infect the three tomato cultivars, whereas ToLCNDV-ES could not. Genome-exchange of the two ToLCNDVs revealed the ToLCNDV DNA-A segment as the main factor for ToLCNDV infectivity in tomato. In addition, serial clones with chimeric ToLCNDV-In A and ToLCNDV-ES A genome segments were generated to identify the region determining viral infectivity in tomatoes. A chimeric clone carrying the ToLCNDV-In coat protein (CP) exhibited pathogenic adaptation in tomatoes, indicating that the CP of ToLCNDV is essential for its infectivity. Analyses of infectious clones carrying a single amino acid substitution revealed that amino acid at position 143 of the CP is critical for ToLCNDV infectivity in tomatoes. To better understand the molecular basis whereby CP function in pathogenicity, a yeast two-hybrid screen of a tomato cDNA library was performed using CPs as bait. The hybrid results showed different interactions between the two CPs and Ring finger protein 44-like in the tomato genome. The relative expression levels of upstream and downstream genes and Ring finger 44-like genes were measured using quantitative reverse transcription PCR (RT-qPCR) and compared to those of control plants. This is the first study to compare the biological features of the two ToLCNDV strains related to viral pathogenicity in the same host plant. Our results provide a foundation for elucidating the molecular mechanisms underlying ToLCNDV infection in tomatoes.